2020
DOI: 10.1002/ptr.6857
|View full text |Cite
|
Sign up to set email alerts
|

Arenaria kansuensis attenuates pulmonary fibrosis in mice via the activation of Nrf2 pathway and the inhibition of NF‐kB/TGF‐beta1/Smad2/3 pathway

Abstract: Pulmonary fibrosis is a key feature of COVID‐19, Chinese herbal medicine Arenaria kansuensis has been used for curing pulmonary disease and antivirus for a long time and it has the potential against COVID‐19. In this work, protective effect of A. kansuensis ethanol extract (AE) on pulmonary fibrosis was evaluated through paraquat (PQ)‐induced pulmonary fibrosis animal model. Results showed that AE could significantly improve the survival rate, increase the body weight and reduce the lung index of mice at the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 40 publications
0
19
0
Order By: Relevance
“…On the other hand, LPS activation in vitro inhibits TGF-β1 production [ 48 ], consistently with the very low amount of TGF-β1 found in our LPS-activated fibroblasts. However, despite the inhibiting effect of LPS, 10 μg O 3 proved to be capable of increasing TGF-β1 secretion also in LPS-activated fibroblasts; on the contrary, 20 μg O 3 and 30 μg O 3 treatments induce a higher stress and a stronger TGF-β1 inhibition, likely due to the activation of the Nrf2/ARE-mediated antioxidant signaling [ 76 , 77 , 78 ]. The stimulating effect of low O 3 concentrations on TGF-β1 secretion observed in our in vitro model is consistent with the upregulation of this cytokine reported in cutaneous wounds undergoing accelerated repair following ozonated oil treatment [ 79 , 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, LPS activation in vitro inhibits TGF-β1 production [ 48 ], consistently with the very low amount of TGF-β1 found in our LPS-activated fibroblasts. However, despite the inhibiting effect of LPS, 10 μg O 3 proved to be capable of increasing TGF-β1 secretion also in LPS-activated fibroblasts; on the contrary, 20 μg O 3 and 30 μg O 3 treatments induce a higher stress and a stronger TGF-β1 inhibition, likely due to the activation of the Nrf2/ARE-mediated antioxidant signaling [ 76 , 77 , 78 ]. The stimulating effect of low O 3 concentrations on TGF-β1 secretion observed in our in vitro model is consistent with the upregulation of this cytokine reported in cutaneous wounds undergoing accelerated repair following ozonated oil treatment [ 79 , 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…These activated fibroblasts cause abnormal repair of the alveolar epithelium, which leads to further fibroblast activation [ 69 ]. It has been suggested that TGF-β plays a central role in the pathogenesis of PF by promoting the activation, proliferation, and differentiation of epithelial cells and myofibroblasts [ 70 ]. Researchers have been working on moving the TGF-β pathway ‘from bench to bedside’.…”
Section: Eets and Fibrosismentioning
confidence: 99%
“…Therefore, Cui et al have recently evaluated the protective capacity of Arenaria kansuensis ethanol extract (AE) on pulmonary fibrosis in paraquat (PQ)-induced pulmonary fibrosis animal models. The study results reveal improved destruction degree of lung tissue structure with increasing AE dosage, reduced collagen deposition in lung interstitium, and reduced degree of inflammatory infiltration and inflammatory cytokines; indeed, the protective effect of AE on pulmonary fibrosis was partly due to activation of Nrf2 pathway and the inhibition of NF-kB/TGF-β1/Smad2/3 pathway [ 160 ]. Another herbal therapy, Shufeng Jiedu has been also suggested as a promising drug for the treatment of COVID-19 demonstrated in the HCoV-229E mice model of lung index.…”
Section: Phenolic Phytochemicals and Phenolic Rich Herbal Medicine Against Coronavirus-associated Lung Injurymentioning
confidence: 99%